IMPLEMENTASI MODEL INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN UNTUK MENDESKRIPSIKAN KETERAMPILAN KOMUNIKASI ILMIAH SISWA - Baiq Muli Harisanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
Verbal scientific communication skills observed in this study include: asking questions, answering questions, contributing ideas / opinions, responding to other students' opinions, and conveying the results of the discussion. Based on the results of the study concluded that the oral communication skills of Al-Azhar Kayangan high school students through learning the integration model of local wisdom are still in the low category. A skill cannot be taught in a short time so it needs to be practiced repeatedly so that students become more skilled. Further research is needed to be related to non-verbal communication skills at the same location and students so that observation of students' communication skills is more comprehensive.